PERKAWINAN ADAT MERARIQ SALAH TADAH BERDASARKAN PERSPEKTIF HUKUM ISLAM: Studi Kasus di Desa Pengembur, Kecamatan Pujut, Kabupaten Lombok Tengah - Mawardi Mawardi (LP2M Universitas Ibrahimy, 2024)
Allah SWT created humans in pairs and cannot live without other people. The way to realize this is, of course, in a good way so that in Islam, the best path is shown for humans (men and women). The best path is a Merariq, where when the person takes the straight path then he will be free from sin and the wrath of Allah SWT. In responding to Merariq as a path that is approved by Allah SWT, Muslims who live in Indonesia, in general, and Muslims who live on the island of Lombok, in particular, have different ways, styles, and cultures of implementing marriage. One of these customary processions is the custom of wrong Tadah marriage that occurs when there is a wedding. What is meant by this researcher is, first, how is the practice of the Merariq wrong Tadah custom in Pengembur Village, Pujut District, Central Lombok Regency. Second: what is the perspective of Islamic law on the Merariq wrong Tadah custom with the concept of Kafa'ah in marriage in Pengembur Village, Pujut District, Central Lombok Regency. To facilitate understanding in this study, the researcher uses research methods, including increasing the exploration of data sources from various works of literature related to the Merariq salah Tadah custom, while the data is obtained by the researcher in the field by conducting interviews, observations, and documentation. After discussing the problems studied, the researcher can conclude that first, the wrong marriage in the custom is required by custom to the party who has violated the agreed custom. Second, according to the perspective of Islamic law, the wrong marriage is permitted as long as there is no prohibition in the sharia that is violated. The wrong marriage custom, which is binding based on custom (‘Urf), is called binding because of the good tradition that has been agreed upon together.